U.S. Policy Towards Azerbaijan (1991-2001) - Mansour , Dr. Nasser Thajeel (Thi Qar Arts Journal, 2024)
The research provides a comprehensive study of U.S. policy towards Azerbaijan during the period 1991-2001, considering the political, diplomatic, and economic dimensions of this policy. It emphasizes a thorough understanding of the factors that influenced U.S.-Azerbaijani relations and the nature of their shared interests, which were characterized by an increased focus on regional stability and economic partnership over a decade. From 1991 to 2001, the United States underwent a transformation in its policy towards Azerbaijan, marked by a heightened focus on achieving American interests in the Caspian Sea region. The main objectives of both countries in establishing their relations were presented, highlighting the pivotal role of the United States and the factors that influenced U.S.-Azerbaijani relations, particularly in the economic sphere, where the energy sector played a major role. This included trade and investment, especially contracts for the extraction and export of Azerbaijani oil to Europe and investments by American oil companies in Azerbaijan.